A note on identification of discrete choice models for bundles and binary games - Jeremy T. Fox; Natalia Lazzati (Quantitative Economics, 2017)
We study nonparametric identification of single-agent discrete choice models for bundles (without requiring bundle-specific prices) and of binary games of complete information. We show that these two models are quite similar from an identification standpoint. Moreover, they are mathematically equivalent when we restrict attention to the class of potential games and impose a specific equilibrium selection mechanism in the data generating process. We provide new identifica- tion results for the two related models.
Keywords: C14; C35; C57; C72; 330; Discrete choice; demand; binary games; identification; bundles; complements; substitutes; entry games; potential games